2018
DOI: 10.1371/journal.pone.0208388
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric relationship of urbanization and CO2 emissions in less developed countries

Abstract: Understanding the relationship between carbon dioxide (CO2) emissions and the urbanization of national populations has been a key concern for environmental scholars for several decades. Although sophisticated modeling techniques have been developed to explore the connection between increases in urban populations and CO2 emissions, none has attempted to assess whether declines in urbanization have an effect on emissions that is not symmetrical with that of growth in urbanization. The present study uses panel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 37 publications
5
32
1
2
Order By: Relevance
“…Whatever the mechanism, this study presents evidence of an urban scale advantage for homicides. Additionally, in light of the relevance of urbanization for sustainability research [2,3,25], we also outlined this finding as a constructive piece of the emerging literature on the link between crime and sustainability [8]. Indeed, the concepts behind all the predictor variables used in our analysis play important roles in a range of theories on development and sustainability; therefore, to improve estimation and generalizability, future cross-national research on these topics can utilize SEM with the FIML option.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Whatever the mechanism, this study presents evidence of an urban scale advantage for homicides. Additionally, in light of the relevance of urbanization for sustainability research [2,3,25], we also outlined this finding as a constructive piece of the emerging literature on the link between crime and sustainability [8]. Indeed, the concepts behind all the predictor variables used in our analysis play important roles in a range of theories on development and sustainability; therefore, to improve estimation and generalizability, future cross-national research on these topics can utilize SEM with the FIML option.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, looking at the quantitative research, the environmental consequences of these different dimensions of urbanization are not identical; they are unevenly associated with environmental change. As seen in the cross-national literature [25], much research has found a positive association between the general level of urbanization of a country and its per capita fossil fuel use. That is, compared to rural areas, urban areas have more productive and consumptive activities transpiring over a longer period of the day, which results in an increased use of fossil fuels.…”
Section: The Multiple Dimensions Of Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also found positive effect of economic growth and CO 2 emission in developed, emerging and middle & north African countries [26]. The phenomenal economic growth in the studied countries in last few decades due to industrial and manufacturing booms has increased the demand for energy consumption which results in an increase in CO 2 emissions [4,5,22]. These countries were responsible for almost 18% of total global CO 2 emissions in 2013 from petroleum consumption.…”
Section: Resultsmentioning
confidence: 90%
“…Global warming is a major threat to the world environment and public health [1,2]. The massive industrial revolution in recent years ran by huge consumption of fossil fuels and consequent quick increase in emissions of carbon dioxide (CO 2 ) has led to austere global warming [3][4][5]. The Intergovernmental Panel on Climate Change (IPCC) reported an increase of average surface temperature by 0.6 • C in the twentieth century ascribed to greenhouse gases [2].…”
Section: Introductionmentioning
confidence: 99%